Cervical and Breast Cancer Screening - APPLE, SOPHIA K (Indonesian Journal of Cancer, 2010)
SUMMARY RECOMMENDATION ON WHO SHOULD GET CERVICAL SCREENING TESTÂ full text : http://www.scribd.com/doc/43592934/Cervical-and-Breast-Cancer-Screening